2012
DOI: 10.1155/2012/812386
|View full text |Cite
|
Sign up to set email alerts
|

Sustained High Level of Serum VEGF at Convalescent Stage Contributes to the Renal Recovery after HTNV Infection in Patients with Hemorrhagic Fever with Renal Syndrome

Abstract: To investigate the role of vascular endothelial growth factor (VEGF) in the increased permeability of vascular endothelial cells after Hantaan virus (HTNV) infection in humans, the concentration of VEGF in serum from HTNV infected patients was quantified with sandwich ELISA. Generally, the level of serum VEGF in patients was elevated to 607.0 (542.2–671.9) pg/mL, which was dramatically higher compared with healthy controls (P < 0.001). There was a rapid increase of the serum VEGF level in all patients from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 47 publications
2
23
0
Order By: Relevance
“…VEGF promotes angiogenesis but also induces capillary leakage (46,47). Previous studies have demonstrated the elevation of VEGF levels in HCPS and HFRS patients (48)(49)(50)(51). They observed early and rather localized elevation of VEGF levels and sustained systemic upregulation later in infection.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…VEGF promotes angiogenesis but also induces capillary leakage (46,47). Previous studies have demonstrated the elevation of VEGF levels in HCPS and HFRS patients (48)(49)(50)(51). They observed early and rather localized elevation of VEGF levels and sustained systemic upregulation later in infection.…”
Section: Discussionmentioning
confidence: 96%
“…They observed early and rather localized elevation of VEGF levels and sustained systemic upregulation later in infection. Early in the infection VEGF seems to contribute to hantavirus pathogenesis, whereas VEGF at later time points may contribute to endothelial repair and convalescence (48,50). Local and systemic effects of cytokines may be involved in pathogenesis and repair (52,53).…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al demonstrated that thrombocytopenic disorders, characterized by increased platelet destruction, can exhibit increased levels of plasma VEGF [14]. Although serum VEGF has been shown to be upregulated in HFRS, the severe form of Hantavirus infection [15, 16], little is known about the association between VEGF and thrombocyte counts in NE cases.…”
Section: Introductionmentioning
confidence: 99%
“…17 Like dengue fever, the critical patients with HFRS typically appear to have a leukemoid reaction, severe plasma leakage, changes in capillary permeability and thrombocytopenia, which could influence the degree of clotting directly and indirectly and increase the probability of multiorgan bleeding and DIC. 6,18 It has been accepted that thrombocytopenia is most likely the result of decreased platelet production or increased platelet destruction and platelet dysfunction. 19,20 Heparin is an important anticoagulant in blood purification because of its low cost and easy monitoring, but it is associated with several negative characteristics and adverse effects, such as heparin-induced thrombocytopenia (HIT) and hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…5 Typical patients progress through the following five successive phases: febrile, hypotensive, oliguric, diuretic and convalescent. 6,7 In some severe and critical cases, the febrile, hypotensive and oliguric phases can overlap during the acute stage, resulting in acute kidney injury (AKI), acute respiratory distress syndrome (ARDS), acute progressive noncardiogenic pulmonary edema, disseminated intravascular coagulation (DIC) and multiple organ dysfunction syndrome (MODS), with increasing hospital fatality remarkably without effective treatment.…”
mentioning
confidence: 99%